2007
DOI: 10.5704/moj.0705.003
|View full text |Cite
|
Sign up to set email alerts
|

Bone Overgrowth after Fracture of the Femoral Shaft in Children

Abstract: Forty children treated non-operatively for fractures of the femoral shaft were reviewed with regard to differences in limb length after treatment. Follow up duration ranged from two to seven years. The average femoral overgrowth was 0.85cm (range 0 -2.5cm) and was influenced by age at the time of fracture. We were not able to find any association between the quantity of overgrowth and race, gender, level or configuration of the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
3
1
Order By: Relevance
“…This may parallel the current study, as growth disturbance was more likely to occur if the patient was younger at the time of injury. 30 Interestingly, in the current study in the entire cohort, there was a correlation between age at the time of surgery and occurrence of growth disturbance but not in the cohort younger than the age of 13 years. Due to the scarcity of literature on this complication, risk of age and growth disturbance has not been discussed in cohort studies to this point.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This may parallel the current study, as growth disturbance was more likely to occur if the patient was younger at the time of injury. 30 Interestingly, in the current study in the entire cohort, there was a correlation between age at the time of surgery and occurrence of growth disturbance but not in the cohort younger than the age of 13 years. Due to the scarcity of literature on this complication, risk of age and growth disturbance has not been discussed in cohort studies to this point.…”
Section: Discussioncontrasting
confidence: 66%
“…Overgrowth of an injured extremity may be observed in other pediatric injuries and is a well-known phenomenon in femoral shaft fractures. 16 , 30 However, it is much less commonly investigated in tibia fractures, especially tibial spine fractures. The mechanism of overgrowth of the injured leg is unclear, both in the current study as well as in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted in 58 children with femoral fracture concluded that overgrowth after fracture of the femur in children is a universal phenomenon. 25 The study also added that a mean increase in length of 0.85 cm could be expected in the affected femur although those below 2 years old had less potential for such overgrowth . According to another study, the overgrowth continued after fracture healing for a limited time period, then ceased with no change in discrepancy throughout the remainder of skeletal growth.…”
Section: Discussionmentioning
confidence: 99%